The structural basis for CD36 binding by the malaria parasite - Fu-Lien Hsieh (Nature Portfolio, 2016)
Targeting of the CD36 scavenger receptor by the malaria parasite effector PfEMP1 prevents splenic clearance of infected erythrocytes. Here, the authors propose that diverse PfEMP1 achieve this by binding to a conserved phenylalanine residue in CD36 that is also required for lipoprotein binding.